Developing Holistic Gasing Evaluation Model to Balance Cognitive Efficiency and Affective Resilience - Ninik Wijiningsih; Eva Puspitasari; Budi Setiawan; Mario Emilzoli (Journal Evaluation in Education (JEE), 2026)
Purpose of the study: The Gasing method (Gampang, Asyik, Menyenangkan) emphasizes ease and enjoyment, yet evaluations frequently neglect the core pillar of enjoyment. This research aims to construct and validate the Holistic Gasing Evaluation Model (HGEM) to balance cognitive speed with affective resilience, making instructional claims of joy empirically verifiable. Methodology: This study utilizes a Type 2 Design and Development Research approach. The procedure involves a systematic analysis of eighty-three empirical papers via Publish or Perish software. A conceptual design phase synthesizes identified theoretical references to establish thirty-six specific model sub-indicators. The final development phase employs the Aiken method with three doctoral experts to validate the model content and structural integrity. Main Findings: The Holistic Gasing Evaluation Model establishes five core dimensions supported by thirty-six psychometric sub-indicators, replacing anecdotal observations with validated instruments like the Mathematics Anxiety Rating Scale. Results show a mean Aiken’s V of 0.86. Discussion indicates that standardizing these metrics identifies instructional risks when rapid speed gains correlate with elevated anxiety, ensuring sustainable numerical performance. The primary limitation of this developmental phase is the focus on internal content validation without immediate large-scale longitudinal field data. Novelty/Originality of this study: This research introduces the first psychometrically validated Affective-Safety guardrail for Gasing evaluation, directly resolving the "Joy Paradox" where anecdotal claims of enjoyment lack empirical verification. By transitioning from qualitative narratives to rigorous standardized benchmarks, this study advances knowledge by ensuring that rapid computational gains do not compromise student affective well-being through replicable assessment protocols.